EVALUATION OF THE EFFECTIVENESS OF THE TECHNICAL CHARACTERISTICS OF TAEKWONDO AS PART OF THE MODEL CHARACTERISTICS OF THE COMPETITIVE EVENT - SPARRING IN TAEKWONDO - A. Asenov (Trakia Journal of Sciences)
The systems for reporting points in taekwondo are changing. That requires rethinking the effectiveness of technical-tactical characteristics. The most significant model characteristics of Taekwondo are derived through expert evaluations and adapted to the features of the recently introduced electronic system for reporting points Daedo Gen 2. Two types of characteristics are presented: technical and tactical. The derived Taekwondo model characteristics are the basis for determining the most important qualities in that sport and for creating a training methodology which could stimulate, develop and improve these particular qualities.